Upaya Menumbuhkan Rasa Percaya Diri Remaja - Claudiya Novita Simanjuntak, Santa; Putra Kasea Sinaga, Randa (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
Practicum activities are one of the mandatory courses that prospective social worker students in the USU FISIP Social Welfare Study Program must take. Field Work Practice 2 is carried out in full for one semester for 1 student (full block placement). Self-confidence is the ability to be confident in the abilities we have or the ability to develop positive judgments both for ourselves and the environment around us. Of course, everyone has their own abilities, but not everyone realizes this or some people don't even believe in their abilities. Problems of not having self-confidence will hinder his development in socializing, developing his potential, getting to know himself, and other developmental tasks. This problem of lack of self-confidence is known to be the result of negative thoughts which have an impact on adolescent behavior. A person who gets self-confidence from other people feels that he is valued, respected, feels that other people are acting responsibly. Everyone needs to have self-confidence so that they understand that each individual has competencies that are useful and useful in their lives. Apart from that, self-confidence must also be at the right level, neither less nor more. The development of self-confidence has a slight change in terms of stopping comparing oneself with others and developing a more positive mindset